Association of Admission Blood Glucose Level with Major Adverse Cardiac Events in Acute Coronary Syndrome; a Cohort Study - Alavi-Moghaddam, Mostafa; Parsa-Mahjoub, Mohammad; Ghodssi-ghassemabadi, Robabeh; Bitazar, Bita (Archives of Academic Emergency Medicine, 2019)
Introduction: Appropriate management of abnormal admission blood glucose level (ABGL) in acute coronary syndrome (ACS) patients still remains a common issue. This study aims to assess the influence of ABGL on development of 30-day major adverse cardiac events (MACEs) in patients with suspected ACS. Methods: This is a prospective cohort study based on analysis of data collected from patients suspected to acute coronary syndrome admitted to emergency department. ABGL of patients was measured and its association with development of MACEs (MI, CVA, mortality) within 30 days of follow-up was studied. Results: 814 participants with the mean age of 61.8 ±13.4 years were studied (58.1% male). MACE endpoints were developed in 166 (39.0%) hyperglycemic, 30 (46.9%) hypoglycemic, and 53 (16.4%) normoglycemic patients (p<0.0001). Mean admission blood glucose level of patients who developed MACE within 30 days was significantly higher than others (210.6±123.4 vs 157.4±86.6mg/dL; p<0.0001; OR: 1.006 (1.005 to 1.008)). There was a significant correlation between male gender (p=0.027), abnormal admission blood glucose level (p<0.001), diabetes (p = 0.001), hypertension (p=0.059), prior CABG (p=0.008), first and second blood troponin levels (p<0.001), first and second abnormal ECGs (p<0.001), and also ECG changes (p<0.001) with developing AMCE. Abnormal ABGL, first and second blood troponin levels, and the history of diabetes were among independent risk factors of developing MACE within 30 days. Conclusion: It seems that abnormal admission blood glucose level in suspected ACS patients was an independent predictor of major adverse cardiac events within 30 days.